First principle study of structural, electronic, mechanical, dynamic and optical properties of half-Heusler compound LiScSi under pressure - Ciftci, Yasemin O.; Evecen, Meryem (Phase transitions, 2018)
In this study, several physical properties of LiScSi compound with MgAgAs phase were investigated via the plane-wave pseudo-potential technique in density functional theory (DFT). The calculated total energy-atomic volume was fitted to the Murnaghan equation of state in order to obtain bulk modulus, their first derivatives and the lattice constant. These results were compared to findings of recent literature. Afterwards, the partial density of states (PDOS) and charge density differences were used to evaluate the electronic band structure of LiScSi under pressure. By analysing elastic properties (shear modulus, Poisson ratio, Young's modulus, etc.) of the material, it has been shown that MgAgAs phase of the compound is mechanically stable under pressure. Moreover, the dynamical stability of this compound is calculated by means of the phonon dispersion curves and one-phonon DOS. Finally, the optical properties and related parameters (refractive index, dielectric function, and loss function) of LiScSi were examined with subject to different pressures.